Media assistance behavior: a vital support for governmental response to social emergencies - Ruizhi Ji; Chenghu Zhang (Frontiers in Public Health)
IntroductionMedia is key to spreading important information and plays a crucial role in emergency management by reporting promptly and accurately, shaping public opinion, and promoting stability during crises.MethodsThis paper aims to investigate the specific role of the media in aiding the government’s response to social emergencies, drawing on 637 questionnaire surveys to refine the cooperation mechanism between the media and the government.ResultsThe research indicates that the media is instrumental in education, warning, and oversight, and by providing timely and accurate information, it bolsters the public’s capacity for oversight and accountability, thereby advancing media publicity. Media entities should foster the enhancement of the social oversight framework through objective and comprehensive reporting.DiscussionStudies reveal that the media is indispensable in emergency response, significantly contributing to the public’s oversight capabilities. This paper focuses on the various roles of media coverage in emergency governance, especially its effects on oversight duties.